New methodology for calculation of required prestressing levels in continuous precast bridge decks - Carlos Sousa (2013)
The calculation of minimum required prestressing levels in prestressed bridge deck girders is usually governed by serviceability requirements in terms of allowable stress levels. In the case of continuous structures, different quantities of prestressing steels have to be quantified for different critical locations and, owing to the structure hyperstaticity, the prestressing force required for a given critical cross section depends on the quantities of prestressing steels adopted in the remainder of the structure. This paper presents a feasible methodology for quantification of the minimum required prestress forces for different critical cross sections, avoiding the use of iterative procedures. A methodology for taking into account the variability of the structure response, owing to the uncertainty associated with the quantification of creep, shrinkage, and construction timings is also presented. Monte Carlo simulations, based on the Latin Hypercube sampling method, are used in the calculation of the statistical distribution of the long-term structure response. Two case studies are presented to show the relevance of the aforementioned variability and its consequences in terms of minimum required prestressing levels.